Reliability of temperature signal in various climate indicators from northern Europe - Hari, Pertti; Aakala, Tuomas; Hilasvuori, Emmi; Häkkinen, Risto; Korhola, Atte; Korpela, Mikko; Linkosalo, Tapio; Mäkinen, Harri; Nikinmaa, Eero; Nöjd, Pekka; Seppä, Heikki; Sulkava, Mika; et al. (Public Library of Science (PLoS), 2017)
We collected relevant observational and measured annual-resolution time series dealing with climate in northern Europe, focusing in Finland.We analysed these series for the reliability of their temperature signal at annual and seasonal resolutions. Importantly, we analysed all of the indicators within the same statistical framework, which allows for their meaningful comparison. In this framework, we employed a cross-validation procedure designed to reduce the adverse effects of estimation bias that may inflate the reliability of various temperature indicators, especially when several indicators are used in a multiple regression model. In our data sets, timing of phenological observations and ice break-up were connected with spring, tree ring characteristics (width, density, carbon isotopic composition) with summer and ice formation with autumn temperatures. Baltic Sea ice extent and the duration of ice cover in different watercourses were good indicators of winter temperatures. Using combinations of various temperature indicator series resulted in reliable temperature signals for each of the four seasons, as well as a reliable annual temperature signal. The results hence demonstrated that we can obtain reliable temperature information over different seasons, using a careful selection of indicators, combining the results with regression analysis, and by determining the reliability of the obtained indicator.
Keywords: climate indicators; reliability; temperatures; temperature information